2015
DOI: 10.1080/09540105.2015.1086317
|View full text |Cite
|
Sign up to set email alerts
|

The matrix interference to the immunoassay of food samples: The effect of some proteins in aquatic products

Abstract: The elimination of matrix interference is now a task for further development and application of immunoassays. Here the effect of proteins in aquatic samples on immunoassay was investigated by western blotting and competitive indirect enzyme-labeled immunosorbent assay (ci-ELISA). Some proteins in flatfishes interacted with different antibodies, resulting in significant loss of accuracy of the immunoassays. Moreover, these matrix proteins prefer to interact with enzyme-labeled antibodies than label-free ones. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…After 5-sulfosalicylic acid (2% m/v) treatment, more than 99% proteins were removed (Table 1), and correspondingly the matrix effect was observed somewhat slighter than that in the original extracts ( Figure 2). Similar to the previous study for ELISA (Wang et al, 2016), in which some matrix protein of fishery extracts were found to react with IgG (especially enzyme-labelled antibodies), here the protein-induced matrix effect may also be attributed to its non-specific binding with the gold-labelled antibodies. This protein-IgG interaction demonstrated no significant affluence on the gold-labelled antibody for its reaction with the secondary antibody on the control line, however, significantly reduced its efficiency to bind with the antigens on the test line.…”
Section: Effect Of Protein Components On the Gicasupporting
confidence: 84%
See 3 more Smart Citations
“…After 5-sulfosalicylic acid (2% m/v) treatment, more than 99% proteins were removed (Table 1), and correspondingly the matrix effect was observed somewhat slighter than that in the original extracts ( Figure 2). Similar to the previous study for ELISA (Wang et al, 2016), in which some matrix protein of fishery extracts were found to react with IgG (especially enzyme-labelled antibodies), here the protein-induced matrix effect may also be attributed to its non-specific binding with the gold-labelled antibodies. This protein-IgG interaction demonstrated no significant affluence on the gold-labelled antibody for its reaction with the secondary antibody on the control line, however, significantly reduced its efficiency to bind with the antigens on the test line.…”
Section: Effect Of Protein Components On the Gicasupporting
confidence: 84%
“…Proteins contribute much of the water-soluble components in the fish crude extracts (Table 1). In previous studies, the interference of matrix proteins to ELISA has been fully confirmed by its possible competitive interaction with antibodies (Wang et al, 2016). In this study, we have verified the influence of proteins on GICA.…”
Section: Effect Of Protein Components On the Gicasupporting
confidence: 74%
See 2 more Smart Citations
“…For example, serum proteins could bind to analytes or the microplate surface (12) and allergens from codfish could bind with the monoclonal anti-parvalbumin antibody (13). In our previous study (14,17), a significant interference (p<0.05) with the immunoassay of norfloxacin was observed in the presence of flatfish matrix, and two protein components with approximate molecular weight of 42 and 36 kD, respectively, were demonstrated to effectively interact with the IgG reagents used in ELISA; therefore, they were assumed to contribute to the matrix effect investigated. However, the physical, chemical, and biological properties of the proteins are still very limited.…”
Section: Introductionmentioning
confidence: 99%